BEHAVIORAL ACTIVITY OF RATS IN THE «OPEN FIELD» AFTER THE LIGHT AND DARK DEPRIVATION AND PHYSICAL EXHAUSTION - A. A. Gostyukhina; T. A. Zamoshchina; M. V. Svetlik; O. B. Zhukova; K. V. Zaitsev; N. G. Abdulkina (Бюллетень сибирской медицины)
Aim. As is known, various stressful loads and their combination lead to unequal direction and degree of psychological and emotional instability. In this regard, one of the pressing issues becomes regulation and correction of psycho-emotional conditions of the person in the complicated conditions of activity, such as athletes during training and competition. To develop appropriate stress-corrective programs should their experimental validation. Therefore, the aim of this study was to investigate the behavioral activity of rats in the “open field” after dark or light deprivation and physical fatigue.Materials and methods. The experimental study was performed on the 40 adult male rats “Wistar”. The experimental groups for 10 days were kept in an artificial bright light (150 lx) or darkness (2–3 lx) for the induction of desynchronozes. Method of forced swimming until complete exhaustion was chosen for the model of physical fatigue. The animals in all groups evaluated behavioral activity in the “open field” in daylight conditions after 24 h after swim test.Results. It was established that in the control group in the terms of natural lighting day after 5 days of daily physical activity occurred depression of the active-search behavior in the “open field”. It was expressed in reducing the number of crossed squares and vertical struts in comparison to intact animals receiving no load. In the groups of animals, which kept in a dark or light deprivation until the presentation of the swim test there was an increase in passive-defensive behavior in the “open field”, which was reflected in an increase in acts of grooming and defecation.